Efficacy of CPP-ACP and CPP-ACPF on enamel remineralization - An in vitro study using scanning electron microscope and DIAGNOdent® - Jayanth Jayarajan; P Janardhanam; P Jayakumar; Deepika (Indian Journal of Dental Research, 2011)
Introduction: Remineralization as a treatment procedure has received a lot of attention both from clinicians as well researchers. The objective of this in vitro study was to find out the efficacy of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) in remineralizing enamel surface on which artificial caries lesion had been created. The changes were analyzed using DIAGNOdent® (KaVo) and scanning electron microscope (SEM). Materials and Methods: Ninety maxillary premolars were selected and divided into three groups of 30 teeth each: A (artificial saliva), B (CPP-ACP), and C (CPP-ACPF). All the samples were assessed using DIAGNOdent® at the baseline and after demineralization and remineralization. Three samples were randomly selected from each group after remineralization for surface evaluation using SEM. Results: Statistical analysis showed that group B {CPP-ACP (4.1±1.8)} and group C {CPP-ACPF (4.8±1.2)} had a significantly higher amount of remineralization than group A (1.7±0.7). Conclusion: All the three groups showed a statistically significant amount of remineralization. However, because of the added benefit of fluoride (NaF 0.2%), CPP-ACPF (Tooth Mousse-Plus®) showed marginally more amount of remineralization than CPP-ACP (Tooth Mousse®).